OPTIMIZING INVENTORY MANAGEMENT USING THE EOQ MODEL: CASE STUDY IN ONE OF THE BANKS IN INDONESIA - Tamaputra, Reza Satria; Farmaciawaty, Desy Anisya (Journal of Research in Social Science and Humanities, 2025)
Efficient inventory management is essential for maintaining operational excellence, particularly in the banking sector, where stock imbalances can disrupt workflows and impact service quality. This study examines inventory practices in of the Indonesia banking sector focusing on challenges like overstock and understock. Using the Economic Order Quantity (EOQ) model, the research determines optimal order quantities, safety stock, and reorder points for selected items. Analysis reveals that 27% of items were overstocked, incurring high holding costs, while understock situations disrupted operations. Root Cause Analysis (RCA) identified issues such as inefficient procurement processes and limited warehouse capacity. Recommendations include automation of inventory systems, improved procurement strategies, and optimized stock levels to enhance operational efficiency. These solutions contribute to reducing costs, improving service quality, and ensuring seamless operations.